Germinal center‐derived lymphomas: The darkest side of humoral immunity - Mlynarczyk, Coraline (Immunol Rev, 2019)
One of the unusual features of germinal center (GC) B cells is that they manifest many hallmarks of cancer cells. Accordingly, most B‐cell neoplasms originate from the GC reaction, and characteristically display abundant point mutations, structural genomic lesions, and clonal diversity from the genetic and epigenetic standpoints. The dominant biological theme of GC‐derived lymphomas is mutation of genes involved in epigenetic regulation and immune receptor signaling, which come into play at critical transitional stages of the GC reaction. Hence, mechanistic studies of these mutations reveal fundamental insight into the biology of the normal and malignant GC B cell. The BCL6 transcription factor plays a central role in establishing the GC phenotype in B cells, and most lymphomas are dependent on BCL6 to maintain survival, proliferation, and perhaps immune evasion. Many lymphoma mutations have the commonality of enhancing the oncogenic functions of BCL6, or overcoming some of its tumor suppressive effects. Herein, we discuss how unique features of the GC reaction create vulnerabilities that select for particular lymphoma mutations. We examine the interplay between epigenetic programming, metabolism, signaling, and immune regulatory mechanisms in lymphoma, and discuss how these are leading to novel precision therapy strategies to treat lymphoma patients.